FERMENTASI SUBSTRAT PADAT BUAH PISANG DAN APLIKASINYA - Anny S.; Lindajati T.; Milono p.; Roestamsjah Roestamsjah (Jurnal Kimia Terapan Indonesia, 1991)
This study is aimed at exploring the posibility of preparing tape pisang by solid substrate fermentation method and applying the results for snack foods preparation. Two varieties of banana i.e. "kepok" (Musa paradisiaca ssp normalis) and "ambon" (Musa paradisiaca ssp sapientum) were used in this experiment. After peeling, steaming and cooling to room temperature the banana was inoculated with yeast, strain Y-8 and Y- 11 isolated from commercial yeast for bread and tape. The incubation was  done for 3 days ill bottles of 500 ml capacity at room temperature, under semi-aerobic condition.Ln this experiment effect of the type of inocula and substrate forms on the quality of tape plsang were . studied Fermentation process was monitored by observing the changes ill total sugar. starch and alcohol content. Results of the study showed that whole "kepok" banana inoculated wiith yeast strain Y-11 produced a good tape pisang with a sweet. slightly sour and alcoholic taste after 2 days of fermentation, containing starch of 14 %, sugar 21.77 %, and 0.05 % alcohol. The "ambon" bananaproduced lB % of alcohol content after two days. the tape has a too soft texture and less attractive appearance. The yeast strain Y-I1 produced better tape plsang than the strain Y-8. 17,e substrate [orm has influenced the sugar content of the tape produced, and the whole form has produced tape with the best texture and appearallce. The results of organoleptic test by panelist all some typical jam and cakes prepared from tape pisang kepok showed satisfactory acceptability.